2021
DOI: 10.1080/19420862.2021.1874121
|View full text |Cite
|
Sign up to set email alerts
|

Brain pharmacokinetics of anti-transferrin receptor antibody affinity variants in rats determined using microdialysis

Abstract: Receptor-mediated transcytosis (RMT) is used to enhance the delivery of monoclonal antibodies (mAb) into the central nervous system (CNS). While the binding to endogenous receptors on the brain capillary endothelial cells (BCECs) may facilitate the uptake of mAbs in the brain, a strong affinity for the receptor may hinder the efficiency of transcytosis. To quantitatively investigate the effect of binding affinity on the pharmacokinetics (PK) of anti-transferrin receptor (TfR) mAbs in different regions of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In addition to classical ADME studies, generation of in silico physiologically based pharmacokinetic (PBPK) models by incorporating PKPD data and safety profiles as a tool for the treatment of CNS diseases has attracted great interest from pharmaceutical scientists and are likely to be crucial to the development of novel antibody-based therapeutics [ 28 , 29 , 108 , 109 , 110 , 111 ]. Further, the high-throughput and low-cost nature of these models permit a more streamlined drug development process in which the identification of antibody structural optimization can be guided based on a parallel investigation of CNS uptake and safety, along with activity [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to classical ADME studies, generation of in silico physiologically based pharmacokinetic (PBPK) models by incorporating PKPD data and safety profiles as a tool for the treatment of CNS diseases has attracted great interest from pharmaceutical scientists and are likely to be crucial to the development of novel antibody-based therapeutics [ 28 , 29 , 108 , 109 , 110 , 111 ]. Further, the high-throughput and low-cost nature of these models permit a more streamlined drug development process in which the identification of antibody structural optimization can be guided based on a parallel investigation of CNS uptake and safety, along with activity [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the lack of availability until recently of large molecular weight cutoff (MWCO) probes and the need for a complicated push–pull system to perform microdialysis with large pore probes [ 27 ]. Although the push–pull microdialysis procedure for antibodies is challenging and requires extensive training, recent studies have shown that it can provide direct in vivo measurement of free antibody concentration in selected regions of the brain in freely moving animals [ 28 , 29 ]. This technique can avoid the detection of bound antibodies to the brain capillary endothelial cells and the neurons, and readouts of free antibody concentration in the brain interstitial ISF tend to better represent the required therapeutic concentration at the site-of-action in the brain.…”
Section: Current In Vitro and In Vivo Methodologies For Measuring Brain Access Of Antibodies: Advantages And Limitationsmentioning
confidence: 99%
“…RMT-based antibody delivery has gained momentum as a viable method to treat central nervous system (CNS) disorders [78,[165][166][167][168]. Most of our RMT-based antibody delivery experience was gained from anti-TfR antibodies, which significantly increased antibody brain uptakes compared to the conventional antibodies [78,169]. There is a tradeoff between antibody affinity to TfR and RMT efficiency.…”
Section: Antibody Distribution In the Brainmentioning
confidence: 99%
“…A very-high anti-TfR1 affinity would alter the TfR trafficking and make antibodies trapped in endosomes, reducing RMT efficiency. A bell-shaped relationship between TfR affinity and antibody brain exposure has been well documented [78,169]. Yu et al developed a series of bsAbs to target TfR and beta-secretase 1 (BACE1) with different affinities to TfR [78].…”
Section: Antibody Distribution In the Brainmentioning
confidence: 99%
“…High affinity TfRMAbs have a dissociation constant (K D ) of binding to the TfR ranging from 0.1 to 3 nM [21][22][23][24][25][26][27][28]. Moderate-affinity TfRMAbs have a KD of binding to the TfR ranging from 14 to 76 nM [26,27,[29][30][31][32]. Low-affinity TfRMAbs have a KD of binding to the TfR ranging from 111 to 300 nM [6,20,33,34].…”
Section: Introductionmentioning
confidence: 99%